Pandangan Masyarakat terhadap Makna yang Terkandung dalam Proses Antar Jujuran Suku Banjar - Khairunnisa; Lilik Andaryuni (Bulletin of Community Engagement, 2024)
Marriage is a profound bond between a man and a woman aimed at forming a harmonious, loving, and compassionate family, grounded in the belief in the Almighty God. The Marriage Law No. 1 of 1974 governs marriage as a means to build a happy family, addressing both physical and spiritual needs. In practice, marriage involves the element of dowry or mahar, which varies by region. In Samarinda, the Banjar ethnic group has a tradition called "maantar jujuran," where the dowry is tailored to the bride’s preferences and local cultural practices. This tradition is not merely a requirement but also a symbol of respect and commitment from the groom. The process of delivering the jujuran involves negotiations between the families of the bride and groom to determine the amount and timing of the dowry. This study employs qualitative methods and case study approaches, using descriptive and analytical techniques to explore the maantar jujuran tradition. Although not part of Islamic law, this tradition is significant in Banjar culture as a form of cultural and local wisdom-based da'wah. The findings indicate that maantar jujuran serves as a symbol of commitment and financial support for the newlyweds, while preserving social norms and cultural traditions within the Banjar community.